THE ISSUES OF MANAGING THE EPIDEMIC SITUATION IN THE HEALTH CARE SYSTEM - OLIVÉR HOMICSKÓ, ÁRPÁD (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
In my present study I intended to outline the effect of the epidemic situation on the health care system. Hungarian legal regulations adequately contain the rules on the basis of which the epidemic situation is manageable. It shall be an important aspect that in this context, in addition to state intervention, individuals should also recognize their role and pay attention to the importance of prevention. I believe that one of the most serious challenges for humanity in the coming decades and centuries beyond will be having the ability to anticipate the emerging epidemics appropriately. However, the epidemic situation has also revealed that the advancement of modern technologies, the fast-paced spread of digitalization cannot alone guarantee the safety of future societies, thus both developing the health care systems and recognizing the prominent role of health workers shall be important in the coming period.